Interpretation of Tolerance Verses in the Ministry of Religion's Thematic Interpretation of Inter-Religious Relations - Khairiyah Asri Nasution; Zainal Arifin Zakaria; Jufri Naldo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study examines the interpretation of Qur’anic verses on tolerance according to the Thematic Tafsir of the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag RI). The background of this research lies in the urgent need for a proper understanding of tolerance in Indonesia's pluralistic society and the importance of having an official government-endorsed tafsir as a reference. The research problems include how Kemenag RI interprets verses on tolerance, the principles of tolerance that can be formulated from these interpretations, and the relevance of such interpretations in today’s Indonesian context. This study employs a qualitative method with a library research approach. Primary data is sourced from the Thematic Tafsir published by Kemenag RI, especially the volume(s) relevant to the themes of tolerance and harmony. Data analysis is conducted through a descriptive-analytical approach to understand the interpretations and formulate the principles of tolerance. The findings show that the Thematic Tafsir of Kemenag RI interprets tolerance as a fundamental Islamic value that promotes peaceful coexistence, recognition of differences, and prohibition of religious coercion highly relevant for maintaining harmony in Indonesia. The novelty of this research lies in its specific focus on Kemenag RI’s Thematic Tafsir as the main source, the systematic formulation of tolerance principles derived from it, and the analysis of their relevance in the context of Indonesia’s diversity. Its relevance to the Indonesian context is evident in how the Thematic Tafsir aligns closely with the values of Pancasila, particularly the first and third principles on Divinity and Unity. This interpretation serves as an important official government reference for fostering peaceful interreligious life in Indonesia.